Spatial Representation of the Workspace in Blind, Low Vision, and Sighted Human Participants - Jacob S. Nelson; Irene A. Kuling; Monica Gori; Albert Postma; Eli Brenner; Jeroen B. J. Smeets (i-Perception, 2018)
It has been proposed that haptic spatial perception depends on one’s visual abilities. We tested spatial perception in the workspace using a combination of haptic matching and line drawing tasks. There were 132 participants with varying degrees of visual ability ranging from congenitally blind to normally sighted. Each participant was blindfolded and asked to match a haptic target position felt under a table with their nondominant hand using a pen in their dominant hand. Once the pen was in position on the tabletop, they had to draw a line of equal length to a previously felt reference object by moving the pen laterally. We used targets at three different locations to evaluate whether different starting positions relative to the body give rise to different matching errors, drawn line lengths, or drawn line angles. We found no influence of visual ability on matching error, drawn line length, or line angle, but we found that early-blind participants are slightly less consistent in their matching errors across space. We conclude that the elementary haptic abilities tested in these tasks do not depend on visual experience.